Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I wanted to know if there's any good approaches to these questions

a)By considering $z^9-1$ as a difference of two cubes, write $1+z+z^2+z^3+z^4+z^5+z^6+z^7+z^8$ as a product of two real factors one of which is a quadratic.

b) Solve $z^9-1=0$ and hence write down the 6 solutions of $z^6+z^3+1=0$

c)By letting $y=z+\frac{1}{z}$ and dividing $z^6+z^3+1=0$ by $z^3$, deduce that: $cos\frac{2\pi}{9}+cos\frac{4\pi}{9}+cos\frac{8\pi}{9}=0$

Any help would be greatly appreciated.

share|improve this question
5  
It seems like the questions themselves suggest good approaches to answering them –  muzzlator Apr 4 '13 at 7:35
add comment

2 Answers

Hint: $a^3-b^3 = (a-b) (a^2+a b+b^2)$. Think about this with $a=z^3$ and $b=1$.

share|improve this answer
add comment

(a) \begin{align*} (z - 1)(z^8 + z^7 + \ldots + 1) = z^9 - 1 & = (z^3 - 1)(z^6 + z^3 + 1) \\ & = (z - 1)(z^2 + z + 1)(z^6 + z^3 + 1) \\ \therefore \qquad z^8 + z^7 + \ldots + 1 & = (z^2 + z + 1)(z^6 + z^3 + 1). \end{align*}

(b) The roots of $z^9 - 1$ are $r_n = e^{\frac{2\pi}9ni}$, for $n = 0, \ldots, 8$. Since $r_0 = 1$ is the root of $z - 1$, the other 8 roots are precisely the roots of $z^8 + z^7 + \ldots + 1 = (z^2 + z + 1)(z^6 + z^3 + 1)$. The quadratic $z^2 + z + 1$ has roots $\frac{-1 \pm \sqrt{3}i}{2}$, which are $r_3$ and $r_6$. Therefore, the 6 roots of $z^6 + z^3 + 1$ are $r_1, r_2, r_4, r_5, r_7, r_8$.

(c) \begin{align*} y^3 & = z^3 + 3z + 3\frac 1z + \frac 1{z^3} \\ y^3 - 3y + 1 & = z^3 + 1 + \frac 1{z^3} = \frac{1}{z^3}(z^6 + z^3 + 1) \\ & = \frac{1}{z^3}(z - r_1)(z - r_2)(z - r_4)(z - r_5)(z - r_7)(z - r_8). \end{align*} The roots of $y^3 - 3y + 1$ are $r_i + \frac{1}{r_i}$, but some $r_i$ give the same root because $r_i = \frac{1}{r_{9-i}}$. More precisely, the three roots are $y_1 = r_1 + \frac{1}{r_1} = r_8 + \frac{1}{r_8}$, $y_2 = r_2 + \frac{1}{r_2} = r_7 + \frac{1}{r_7}$, and $y_3 = r_4 + \frac{1}{r_4} = r_5 + \frac{1}{r_5}$.

We also know that the sum of the roots of $y^3 - 3y + 1$ is $0$ because the coefficient in front of $y^2$ is $0$. This means \begin{align*} y_1 + y_2 + y_3 = r_1 + \frac 1{r_1} + r_2 + \frac 1{r_2} + r_4 + \frac 1{r_4} & = 0 \\ 2\left(\cos\frac{2\pi}9 + \cos\frac{4\pi}9 + \cos\frac{8\pi}9\right) & = 0 \end{align*}

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.